2018
DOI: 10.3389/fnmol.2018.00245
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Through GHSR1a and OX1R Heterodimers Reveals a Gαs–cAMP-cAMP Response Element Binding Protein Signaling Pathway in Vitro

Abstract: Growth hormone secretagogue receptor 1α (GHSR1a) and Orexin 1 receptor (OX1R) are involved in various important physiological processes, and have many similar characteristics in function and distribution in peripheral tissues and the central nervous system. We explored the possibility of heterodimerization between GHSR1a and OX1R and revealed a signal transduction pathway mechanism. In this study, bioluminescence and fluorescence resonance energy transfer and co-immunoprecipitation (Co-IP) analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…In this study, using TM and TM‐m peptides as biochemical tools to dissect actions of the SCTR/AT1aR heteromer in PVN, we firstly demonstrate the in vivo actions of SCTR/AT1aR heteromer in regulating plasma Vp release and expression via cFos/cAMP/CREB pathway in magnocellular neurons of PVN. Our data also explain the results of previous studies indicating: 1 ) colocalization of SCTR and AT1aR in PVN, particularly in magnocellular neurons, 2) central actions of ANGII require an intact SCT‐SCTR axis, and 3) actions of the SCTR/AT1aR heteromer are largely dependent on the cAMP pathway (13, 36, 37). Of note, the functional specificity of SCTR/AT1aR heteromer was fully demonstrated by intracerebroventricular injection of STM2 because it can only disrupt SCTR/AT1aR heterodimerization but not SCTR or AT1aR homodimerization.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, using TM and TM‐m peptides as biochemical tools to dissect actions of the SCTR/AT1aR heteromer in PVN, we firstly demonstrate the in vivo actions of SCTR/AT1aR heteromer in regulating plasma Vp release and expression via cFos/cAMP/CREB pathway in magnocellular neurons of PVN. Our data also explain the results of previous studies indicating: 1 ) colocalization of SCTR and AT1aR in PVN, particularly in magnocellular neurons, 2) central actions of ANGII require an intact SCT‐SCTR axis, and 3) actions of the SCTR/AT1aR heteromer are largely dependent on the cAMP pathway (13, 36, 37). Of note, the functional specificity of SCTR/AT1aR heteromer was fully demonstrated by intracerebroventricular injection of STM2 because it can only disrupt SCTR/AT1aR heterodimerization but not SCTR or AT1aR homodimerization.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that GPCRs can activate the PI3K/AKT signaling pathway. For example, orexin receptor (OXR) activation promotes the upregulation of a Gs-cAMP-cAMP-responsive element signaling pathway and plays a key role in the PI3K/AKT signaling pathway [ 52 , 53 ]. The succinate receptor GPR91, a Gi-coupled receptor, can increase intracellular calcium concentrations through PLCb and upregulate the levels of p-Akt/t-Akt in cardiomyocytes [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a G-protein-coupled receptor, GHSR is present mainly existed in the hypothalamus and pituitary [9,28]. Two isoforms of GHSR have been reported [29], GHSR1α [30,31] and GHSR1β [32,33]. However, GHSR1α is responsible for ghrelin-induced endocrine effects and some nonendocrine effects.…”
Section: Ghsr1α Was Expressed In the Mouse Liver And Hepatocytesmentioning
confidence: 99%